Synthesis, Characterization and Biological Activity Studies of Some N-Mannich Bases of 1-Substituted methyl-2-(substituted phenyl)benzimidazoles - Bamnela, Rita; K. Ahirwar, Mukesh; Shrivastava, S.P. (Asian Journal of Chemistry, 2010)
The synthesis of N-Mannich bases of 1-substituted methyl-2-(substituted phenyl)benzimidazoles have been reported. The synthesized derivatives were characterized by elemental analysis and spectral data (IR and 1H NMR). All the synthesized derivatives have been evaluated for their antibacterial, anthelmintic and insecticidal activities against microbes, helminthes and insects as compared to standard drugs. All the synthesized derivatives exhibited significant to good biological activities.